PENGARUH WORK LIFE BALANCE DAN CYBERLOAFING TERHADAP KINERJA : MEDIASI KEPUASAN KERJA KARYAWAN PADA PT. BANK BENGKULU PUSAT - Radjifkhal Shafa Gunares; Nasution Nasution (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2025)
This study aims to provide an analysis regarding the influence of work-life balance and cyberloafing on employee performance, with job satisfaction as a mediating variable at PT. Bank Bengkulu Central Office. This research is a quantitative study using a questionnaire as the data collection method. Data analysis was conducted using SmartPLS version 4.0. The study population consisted of 193 employees at the Central Office of PT. Bank Bengkulu. The sample was determined using the Slovin formula, resulting in 131 respondents selected randomly through a simple random sampling technique from all employees at the bank’s central office. The findings indicate that both cyberloafing and work-life balance have a significant positive effect on employee performance at PT. Bank Bengkulu Central Office, both directly and through the mediating role of job satisfaction. Job satisfaction was also found to significantly affect employee performance. Additionally, work-life balance and cyberloafing behavior have a direct influence on the level of job satisfaction.